Peningkatan pengetahuan, sikap, dan perilaku petugas kesehatan melalui pelatihan keselamatan dan kesehatan kerja - Saipul, Saipul; Salmawati, Lusia; Guli, Musjaya M; Vidyanto, Vidyanto; Miswan, Miswan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Occupational Safety and Health (OSH) is an essential aspect in creating a safe and productive work environment, especially for healthcare workers who are at high risk of occupational accidents and diseases. One of the efforts to increase awareness and implementation of OSH is through training programs. Purpose: This study aimed to determine the effectiveness of Occupational Safety and Health (OSH) training on the knowledge, attitudes, and behaviors of healthcare workers at Sarjo Public Health Center, Pasangkayu Regency. Method: This quantitative study employed a quasi-experimental design using a one-group pretest–posttest approach. The sample consisted of 38 healthcare workers selected by purposive sampling. Data were collected using questionnaires before and after the training, and analyzed using the Wilcoxon Signed Rank Test. Results: The findings showed a significant improvement between pretest and posttest scores on knowledge (p=0.000), attitude (p=0.001), and behavior (p=0.000). Conclusion: The OSH training was effective in enhancing cognitive ability, fostering positive attitudes, and improving safe work practices among healthcare workers at Sarjo Public Health Center. These results are expected to serve as a foundation for continuous OSH training initiatives as a preventive effort toward workplace accidents and the promotion of safety culture in healthcare settings. Keywords: Attitude; Behavior; Healthcare Workers; Knowledge; Occupational Safety and Health Training. Pendahuluan: Keselamatan dan Kesehatan Kerja (K3) merupakan aspek penting dalam menciptakan lingkungan kerja yang aman dan produktif, khususnya bagi tenaga kesehatan yang memiliki risiko tinggi terhadap kecelakaan dan penyakit akibat kerja. Salah satu upaya yang dapat dilakukan untuk meningkatkan kesadaran dan penerapan K3 adalah melalui pelatihan. Tujuan: Untuk mengetahui peningkatan pengetahuan, sikap, dan perilaku petugas kesehatan melalui pelatihan keselamatan dan kesehatan kerja. Metode: Penelitian kuantitatif dengan desain quasi experiment menggunakan rancangan one group pretest–posttest design. Sampel penelitian berjumlah 38 partisipan yang dipilih secara purposive sampling. Pengumpulan data dilakukan melalui kuesioner sebelum dan sesudah pelatihan, kemudian dianalisis menggunakan uji Wilcoxon Signed Rank Test. Hasil: Adanya peningkatan yang signifikan antara sebelum dan sesudah pelatihan pada variabel pengetahuan (p=0,000), sikap (p=0,001), dan perilaku (p=0,000). Simpulan: Pelatihan K3 efektif dalam meningkatkan kemampuan kognitif, membentuk sikap positif, dan memperbaiki perilaku kerja aman petugas kesehatan. Kata Kunci: Pelatihan K3; Pengetahuan; Perilaku; Petugas Kesehatan; Sikap.